The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1186/s12933-018-0708-x
|View full text |Cite
|
Sign up to set email alerts
|

SGLT2 inhibition via dapagliflozin improves generalized vascular dysfunction and alters the gut microbiota in type 2 diabetic mice

Abstract: BackgroundType 2 diabetes (T2D) is associated with generalized vascular dysfunction characterized by increases in large artery stiffness, endothelial dysfunction, and vascular smooth muscle dysfunction. Sodium glucose cotransporter 2 inhibitors (SGLT2i) represent the most recently approved class of oral medications for the treatment of T2D, and have been shown to reduce cardiovascular and overall mortality. Although it is currently unclear how SGLT2i decrease cardiovascular risk, an improvement in vascular fun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
162
4
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 195 publications
(183 citation statements)
references
References 56 publications
(72 reference statements)
12
162
4
5
Order By: Relevance
“…In keeping with the possibility of additional mechanisms, it was recently shown that in obese mice with diabetes resulting from homozygous mutation of the leptin gene (lepr db /lepr db ), treatment with dapagliflozin resulted in improved glycemic control associated with improvement in arterial stiffness and alteration in their microbiome. 76 Whether similar effects will be observed in patients with T2DM remains to be determined. Future research could explore combination of therapeutics that have shown promising results in the treatment of NAFLD in patients with and without T2DM.…”
Section: Future Directions and Conclusionmentioning
confidence: 96%
“…In keeping with the possibility of additional mechanisms, it was recently shown that in obese mice with diabetes resulting from homozygous mutation of the leptin gene (lepr db /lepr db ), treatment with dapagliflozin resulted in improved glycemic control associated with improvement in arterial stiffness and alteration in their microbiome. 76 Whether similar effects will be observed in patients with T2DM remains to be determined. Future research could explore combination of therapeutics that have shown promising results in the treatment of NAFLD in patients with and without T2DM.…”
Section: Future Directions and Conclusionmentioning
confidence: 96%
“…SCFAs could alter the metabolic state via activation of nuclear receptors such as PPARs (Hasan, et al, 2019) or specific GPRs such as GPR41 and GPR43 that are involved in the release of the entero hormone PYY (Samuel, et al, 2008), fat accumulation reduction, energy expenditure (Kimura, et al, 2013) and insulin secretion (Tolhurst, et al, 2012). Several molecules, including GLP-1, MyD88, dipeptidyl peptidase-4 (DPP-4) and sodium glucose cotransporter 2 (SGLT2), interact closely with the gut microbiota to modulate insulin secretion (Grasset, et al, 2017), diabetes-related metabolic effects (Duparc, et al, 2017;Liao, et al, 2019) and diabetes-induced vascular dysfunction (Lee, et al, 2018).…”
Section: Diabetesmentioning
confidence: 99%
“…Помимо этого, было выявлено, что сниженное в группе животных с ожирением и СД2 количество Lactobacillus, Bifidobacterium, как основных продуцентов КЦЖК, нивелировалось в группе Bifidobacterium и оставалось без изменений в группе Lactobacillus [47]. получавших дапаглифлозин, относительно группы контроля, что, вероятно, связано с увеличением продукции КЦЖК, сохранением целостности муцинового слоя и улучшением метаболических результатов [49]. В другом исследовании было показано, что двойной ингибитор НГЛТ-1, -2 снижает уровень глюкозы в крови и уровень HbA 1c и приводит к увеличению содержания ГПП-1 у животных, получающих богатую углеводами пищу.…”
Section: влияние инкретиновunclassified